PP.24.11: PLACENTAL DYSFUNCTION IN THE STROKE PRONE SPONTANEOUSLY HYPERTENSIVE RAT. (June 2015) - Small, H.; Morgan, H.; Delles, C.; Graham, D.
Abstract : Objective: Previously, we have shown that the pregnant SHRSP has deficient uterine artery remodelling relative to the normotensive WKY. We hypothesised this deficient uterine artery remodelling adversely affects placental development and pregnancy outcome in the SHRSP. Design and method: Blood samples were collected at pre-pregnancy then gestational days (GDs) 6, 12 and 18 from WKY (n = 9) and SHRSP (n = 9). Animals were sacrificed on day 18. Placental tissue was dissected into four layers: decidua, junctional zone, labyrinth and chorionic plate. Biomarkers were analysed using ELISA. Results: In maternal plasma, biomarker analysis showed VEGF was not detectable at late pregnancy in both strains – similar to human pregnancy. sFlt-1:PlGF ratio (5.34 ± 0.67 vs. 4.56 ± 0.36) and ET-1 (3.04 ± 0.10 vs. 2.73 ± 0.02 pg/ml) were significantly increased in SHRSP at GD18. Litter size was reduced significantly (8.00 ± 0.38 vs. 11.89 ± 0.65) however fetal weight was not different. Placental morphology in the SHRSP was abnormal, showing reduced weight (0.20 ± 0.01 vs. 0.23 ± 0.01 g) and haemorrhagic areas on visual inspection. We found significantly increased placental expression of genes involved in inflammation (Tnf [decidua RQ 8.20 ± 1.07; labyrinth RQ 7.97 ± 3.27; chorionic RQ 4.27 ± 0.66], Vcam [decidua RQ 4.04 ± 0.68; labyrinth RQ 2.27 ± 0.69]) and hypoxia (Vegf [junctional RQ 1.98 ± 0.30; labyrinth RQ 2.61 ± 0.69], Hif1a [decidua RQ 3.84 ± 0.89; labyrinth RQ 3.83 ± 1.14], Sod1 [decidua RQ 2.08 ± 0.35; labyrinth RQ 1.64 ± 0.04]). There was also an up-regulation of endothelin receptor A (decidua RQ 2.90 ± 0.57; labyrinth RQ 2.16 ± 0.74) and angiotensin receptor 2 (decidua RQ 3.58 ± 0.33; labyrinth RQ 2.77 ± 0.48) in the vascular compartments. Conclusions: In conclusion, there is a modest but significant increase in plasma biomarkers implicated in abnormal human pregnancy as well as the presence of placental dysfunction. Moreover, patterns of placental gene expression align with data from human placenta with hypertensive disorders of pregnancy. The SHRSP is a novel model to study spontaneous abnormal pregnancy without surgical, genetic or pharmacological intervention.